ANALISIS KEBUTUHAN PERALATAN PEMANENAN KAYU: STUDI KASUS DI PT. SURYA HUTANI JAYA, KALIMANTAN TIMUR - Sona Suhartana; Yuniawati (BRIN Publishing, 2017)
Proper quantity of equipments in timber harvesting should be well planned and managed to obtain efficient time and cost of production. This paper study the proper quantity of timber harvesting equipment in accord with production target. The study was conducted in 2010 at PT Surya Hutani Jaya, East Kalimantan. Data collected from the field consisted of equipment productivities, owners and operating costs, number of equipments, and production plan. The collected data were then averaged, and the effects of equipments on productivity and production cost were analyzed using multiple linear regression. Results reveal that there are excessive and shortage uses of equipments in felling to hauling activities, according to the production plan. The most efficient wood harvesting equipments composition for the correlated production consist of 21 units chainsaws for felling, 9 units excavators for skidding, 10 units loaders, 2 units excavator for unloading and 31 units trucks for hauling. The number of timber harvesting equipments has significant influences on harvesting productivity and production cost.